THE POTENTIAL VARIABLES OF FIRST CHILD’S ENVIRONMENTAL QUALITY: A RETROSPECTIVE ANALYSIS FROM 1994 TO 2012 - Rindang Ekawati; Laili Rahayuwati; Atlastieka Praptiwi (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2020)
Aim: This study aimed at comparing predictor variables associated with the environmental quality of first child. Since the beginning of 1987, Indonesian National Family Planning Board (BKKBN) has been discouraging early first marriage (marrying before 20 for females and before 25 for males). In 2016, BKKBN recommended ideal ages of marriage for females and males as old as 21 and 25 respectively. Methodology and Results: This study was a retrospective analysis involving 5 groups of data reported within the period of 1994-1997 (n=34,225), 1997-2000 (n=34,227), 2001-2004 (n=33,088), 2005-2009 (n=40,701), and 2009-2012 (n=45,607). Data were collected from the Indonesian Demographic and Health Survey datasets (SDKI [Survei Demografi dan Kesehatan Indonesia]). Data were analyzed using chi-square tests. Results indicated several variables that significantly contributed to the first child’s environment quality: (1) residential area (p value<0.05); (2) mother’s educational background (p value<0.05); (3) mother’s exposure to information media (p value<0.05); (4) mother’s employment status (significance were only found in two groups of data:  1994-1997 and 1997-2000 with each p value<0.05); (5) father’s educational background (p value<0.05).    Conclusion, significance and impact of study: In conclusion, there was an inconsistency with regard to strong and weak potential factors of first child’s environment quality within an eighteen-year period. It is recommended to reassess the predictors. It is also important to develop strategies to improve marriage quality and family formation.